INDEPENDENSI AUDITOR BERBASIS KULTUR DAN FILSAFAT HERBERT BLUMMER - Kalana, Indriya (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
Independence in carrying out audits is the backbone of a professional auditor. Therefore, theauditor or public accountant is not justified to take side towards anyone. Culture can influencepersonal public accountants or auditors which will affect their attitude of independence. Culturaldifferences also influence the patterns of social interaction. Several studies in the field ofaccounting discussed the perception of auditorâs independence from some parties which reflects theopportunity of arising differences in the understanding auditor independence in thecommunications room. Factors that could cause such differences include the understanding ofculture and personal experience as the result of daily interactions.This is qualitative research by translating/interpreting the word auditor independence as aunit of study (unit of analysis). Study (analysis) of the understanding of auditor independence is notlimited to the definition of auditor independence based on the informants perception alone, but itwas developed to be understood on the influence of culture and social interaction which are ownedby informants in this study. Excavation of subjectivity of the informants was carried out as far aspossible in accordance with the basic theoretical foundation of Herbert Blummer which is"situating" meaning in social interaction.Having carried out a qualitative research process, it appeared a gap between the theories ofindependence that had been granted in education with the real conditions in the field of practice.This gap was obtained by the contact or interviews with informants who are used as source of datain this study. This study implied the need for adjustment of the regulator to address the conditionsthat demand auditorâs tolerance as a result of the influence of culture and social interaction.Keywords: Independence of The Auditor, Culture, Symbolic Interactions, Herbert Blummer Theory,Qualitative Research